CSR in the Russian aviation industry: the winds of change. Issue 8 (13th July 2015) - Mark Thomas, Mr; Belyaeva, Zhanna
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The article outlines strategic corporate social responsibility (CSR) ongoing progress in the aviation industry in Russia as well as its results. Design/methodology/approach – The paper pinpoints some CSR techniques as a response to the drastic changes of the aviation business environment in Russia. The cases are related to four specific Russian airlines. Findings – The revealed paradox reads that passengers choose the cheapest, but the safest company, care for aviation effects on environment and spread all the failure stories faster with social media and networks. CSR in aviation seems to be the improvement driver ensuring stable passenger traffic if applied right. On the other hand, the irresponsible behaviour might cost too expensive in the long run. Practical implications – The paper illustrates some cases on the example of the Russian civic aviation CSR, which uncovers do's and don'ts in applying CSR techniques in the industry. Originality/value – This article suggests how shared value-based strategic responsibility can become powerful risk-management tool for the progressive airlines.